2014
DOI: 10.1103/physrevb.89.174414
|View full text |Cite
|
Sign up to set email alerts
|

Polar and antipolar polymorphs of metastable perovskiteBiFe0.5Sc0.5O3

Abstract: A metastable perovskite BiFe 0.5 Sc 0.5 O 3 synthesized under high-pressure (6 GPa) and high-temperature (1500 K) conditions was obtained in two different polymorphs, antipolar P nma and polar I ma2, through an irreversible behavior under a heating/cooling thermal cycling. The I ma2 phase represents an original type of a canted ferroelectric structure where Bi 3+ cations exhibit both polar and antipolar displacements along the orthogonal [110] p and [110] p pseudocubic directions, respectively, and are combine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 42 publications
7
75
0
Order By: Relevance
“…The part of the antisymmetric exchange related to octahedral tilting was considered in detail in Ref. [17]. It has been shown that the axial distortions associated with the octahedral rotations are responsible for the weak ferromagnetic properties of antiferromagnetically ordered perovskites with a G-type spin configuration.…”
Section: B Magnetic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The part of the antisymmetric exchange related to octahedral tilting was considered in detail in Ref. [17]. It has been shown that the axial distortions associated with the octahedral rotations are responsible for the weak ferromagnetic properties of antiferromagnetically ordered perovskites with a G-type spin configuration.…”
Section: B Magnetic Structurementioning
confidence: 99%
“…On heating, the antipolar P nma phase of BiFe 0.5 Sc 0.5 O 3 was found to transform into the polar R3c phase identical to that of BiFeO 3 . Subsequent cooling below the transition temperature resulted in onset of a polar phase with the I ma2 symmetry, where the ferroelectric-like displacements of Bi 3+ cations along the [110] p pseudocubic direction are combined with the antiphase octahedral tilting about the polar axis [17]. It has also been shown that both the P nma and the I ma2 polymorphs of BiFe 0.5 Sc 0.5 O 3 exhibit a long-range antiferromagnetic ordering with a weak ferromagnetic component below about 220 K. The antiferromagnetic configuration was found to be of a G type (where the Fe/Sc nearest neighbors in all three directions have antiparallel spins).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system demonstrates a rich phase diagram. Three consecutive phases with different crystal structures appear as the lanthanum content is increased: the as-prepared phase with x ≤ 0.05 is an antipolar Pnma [6], an incommensurately modulated phase with the Imma(00γ)s00 superspace group [7] is observed for 0.10 ≤ x ≤ 0.30, and a non-polar Pnma phase [8] is stable at x ≥ 0.35.…”
Section: Introductionmentioning
confidence: 99%
“…Bi 1−x La x Fe 0.5 Sc 0.5 O 3 perovskites are the rare examples of single-phase multiferroics which were recently obtained under high-pressure conditions [6][7][8]. The system demonstrates a rich phase diagram.…”
Section: Introductionmentioning
confidence: 99%